How Expert Special Educators Effectively Negotiate Their Job Demands - Ortogero, Shawna P.; Black, Rhonda S.; Cook, Bryan G. (Journal of the American Academy of Special Education Professionals, 2017)
This qualitative case study explored how three expert secondary special education teachers in Hawaii successfully negotiated their job demands. Purposeful sampling was used to select one secondary school on the Leeward coast of Oahu. We used reputational-case sampling to select participants that fit Dreyfus and Dreyfus’ (1980) expert theoretical construct, and defined expert special education teachers as (a) licensed to teach special education in Hawaii, (b) taught special education in Hawaii for a minimum of 6 years, and (c) nominated by their principals and special education department chair as experts. Data were derived from semi-structured interviews, observations, and teacher-kept time journals and were analyzed through individual and cross-case analysis to uncover underlying themes. Findings from this qualitative study identified resources and supports, skills, behaviors, and dispositions that three expert special education co-teachers used to effectively manage their multiple job demands such that they averted burnout and remained in the field. Major themes regarding what helped the participants juggle their job demands included relying on others for help; working beyond required work hours; multitasking; and having good classroom management skills, a positive attitude, and empathy. These results have implications for teacher education programs, administrators, and practitioners regarding the qualities of expert special educators, how to move from a novice to expert teacher, and providing role clarification.